Life cycle assessment of freight railroads: a critical analysis and guideline proposal - Carvalhaes, Bernardo Bicalho; Calmon, João Luiz; Vieira, Darli Rodrigues; Bravo, Alencar Soares (Brazilian Journal of Production Engineering, 2024)
This study conducts a review of several articles inside the context of railroads, where the life cycle assessment methodology (LCA) is applied. Using the ProKnow-C methodology, seven review and 85 original papers applying the LCA methodology to railroads are analyzed, and several important gaps were identified, mainly concerning the lack of disclosure of information about parameters, software and other important decisions made during the works that would allow other researchers to replicate the results in order to compare them to other railroads or different circumstances. Currently, there are no ISO standards addressing the LCA of railroads, so this work seeks to provide an initial set of guidelines facilitating the elaboration of such a norm and providing support and direction for researchers in the field.
Keywords: life cycle assessment; LCA; freight railroads; guidelines